Budaya Populer Marvel sebagai Arena Dialog Teologi Kristen bagi Pelayanan Kaum Muda - Heryanto Heryanto (STTI Harvest Semarang, 2026)
The dynamics of globalization, alongside advancements in communication technology, have become catalysts for the widespread expansion of popular culture within society. Mass media holds significant authority in constructing consumer trends, particularly among the youth, primarily for commercial interests. This culture transcends mere entertainment; it functions as an instrument that shapes daily attitudes, habits, and behaviors. Theological issues have emerged regarding popular culture disseminated through visual media, such as Marvel films, which present superhero narratives encompassing themes of good, evil, sin, atonement, and salvation—all of which are often juxtaposed with Christian theology. This research explores the popular culture of Marvel films, identifying concepts and doctrines that deviate from Biblical teachings and examining their implications for youth ministry. Employing a qualitative method through literature review and theoretical analysis, this study discusses the Church's stance and three primary strategies to utilize popular culture as a medium for evangelism and a tool for introducing existential issues, ensuring the Church remains relevant without compromising its core doctrinal essence. The findings of this research suggest that the Church can transform these cultural challenges into opportunities to fortify the faith of young people through a steadfast foundation in Jesus Christ as the sole source of authority and true salvation. AbstrakDinamika globalisasi dan kemajuan teknologi komunikasi saat ini menjadi katalisator bagi meluasnya budaya populer di tengah masyarakat. Media massa memiliki otoritas besar dalam mengonstruksi tren yang dikonsumsi masyarakat, terutama kaum muda, untuk kepentingan komersial. Budaya ini bukan sekadar hiburan, melainkan instrumen yang membentuk sikap, kebiasaan, dan perilaku sehari-hari. Munculnya isu-isu teologis seputar budaya populer yang disebarkan melalui media visual seperti film-film produksi Marvel yang menghadirkan kepahlawan super yang berkaitan tema kebaikan, kejahatan, dosa, penebusan hingga keselamatan yang dikaitkan dengan teologi Kristen. Penelitian ini mengeksplorasi budaya populer film-film Marvel yang memiliki konsep dan doktrin yang menyimpang dengan doktrin Alkitab dan implikasinya terhadap pelayanan kaum muda. Penelitian ini menggunakan metode kualitatif melalui kajian pustaka dan analisis teoritis, penelitian ini juga membahas sikap dan tiga strategi utama gereja untuk menjadikan budaya populer sebagai sarana penginjilan dan sarana pengenalan isu eksistensial, gereja dapat tetap relevan tanpa kehilangan esensi doktrin intinya. Temuan penelitian ini dapat dipergunakan gereja untuk mengubah tantangan budaya ini menjadi peluang untuk memperkuat iman kaum muda melalui dasar iman yang kokoh di dalam Yesus Kristus sebagai satu-satunya sumber otoritas dan keselamatan sejati.